IMPLEMENTASI PENAGIHAN PAJAK BUMI BANGUNAN PENCAIRAN PIUTANG DI KECAMATAN KOJA TAHUN 2024 - Acqal Ardinata; Selvi (Jurnal Ilmu Administrasi Publik, 2025)
This study aims to analyze the Implementation of Rural and Urban Land and Building Tax (PBB-P2) Collection in the Context of Receivables Settlement in Koja District in 2024. The background of this research is based on the fluctuation of PBB-P2 revenue realization and the significant increase in tax receivables in 2024. This research uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. Data analysis refers to the Van Meter and Van Horn (1975) policy implementation model, which consists of six variables: policy standards and objectives, resources, implementing organization characteristics, inter- organizational communication, implementers’ disposition, and external environment. The results indicate that the implementation of PBB-P2 collection in Koja District has been relatively effective, as reflected by the achievement exceeding the target in 2023 and 2024. However, there are still obstacles such as low taxpayer awareness, limited human resources, suboptimal data updating, and socio- economic factors affecting taxpayers’ ability to pay. Efforts to overcome these obstacles include increasing public outreach, optimizing cross-sector collaboration, utilizing information technology, and strengthening coordination between tax officers and local government apparatus. This study provides an academic contribution as a reference for local tax collection implementation, as well as practical benefits for the Provincial Government of DKI Jakarta and the Regional Revenue Agency in formulating strategies to improve PBB-P2 receivable settlements.